MICROSTRUCTURE CHANGES IN THE SURFACE LAYERS OF MACROHETEROGENEOUS COMPOSITES UNDER HIGH-ENERGY INFLUENCE - V. A. Kalinichenko; O. G. Devojno; A. S. Kalinichenko (Литьë и металлургия, 2013)
The aim of the work is development of coatings with composite macroheterogeneous structure that are characterized with good antifriction properties and able to perform in severe working conditions. To form coating a CO2-laser was applied.